Impact of ImarsilTM Adsorption on Aflatoxin M1 (AFM1) Levels in Cow's Milk: Analyzing Hematological Parameters and Histopathological Alterations - Kolapo, Adelodun Lawrence; Oluwafemi, Flora; Kareem, Sarafadeen; Fawole, Abosede Oyeyemi; Adejumo, Olufunmilayo Ebunoluwa (Industria: Jurnal Teknologi dan Manajemen Agroindustri, 2023)
Abstract The efficacy of ImarsilTM in mitigating the effects of aflatoxin M1 (AFM1) in cow's milk on hematological and histopathological parameters was investigated in this study. Seventy-two albino rats were randomly allocated to four treatment groups A - D in a six-week study. Rats in all groups were fed standard ration. In addition, 2 mL of clean distilled water, 2 mL of milk, 2 mL of AFM1 contaminated milk (456 ng/L), and 2 mL of AFM1 contaminated milk (456 ng/L) treated with ImarsilTM at 2% dosage rate were added to the ration of animals in groups A, B, C, and D respectively. The results of the investigation showed that rats in Group C developed a significant (p<0.05) lower weight. Packed Cell Volume (%), Hemoglobin (g/dL), Red Blood Cell (106/mm3), Mean Corpuscular Volume (fL), Mean Corpuscular Hemoglobin (pg), and Mean Corpuscular Hemoglobin Concentration (g/dL) were not significantly different (p>0.05) among the different groups. In group C, a significant reduction (p<0.05) occurred in the white blood cell (103/mm3) (12.90 - 8.63), and lymphocytes (87.00 - 74.33%) counts while the neutrophils (%) increased from 13.00 to 25.67. In contrast to those in Group C, tissue sections from Group D showed no histological lesions. Therefore, ImarsilTM represents an effective and safe adsorbent for the remediation of AFM1-contaminated milk.Keywords: adsorbents, aflatoxin M1, cow’s milk, hematological parameters and histopathological changes, ImarsilTM AbstrakTingkat keberhasilan ImarsilTM dalam memitigasi efek aflatoksin M1 (AFM1) pada susu sapi terhadap parameter hematologi dan histopatologi diidentifikasi dalam penelitian ini. Tikus albino 72 ekor secara acak dibagi menjadi 4 kelompok perlakuan A, B, C, dan D dalam penelitian 6 minggu. Tikus pada semua kelompok diberi ransum standar. ImarsilTM dengan dosis 2%. dicampurkan pada 2 mL air suling bersih, 2 mL susu, 2 mL susu terkontaminasi AFM1 (456 ng/L), dan 2 mL susu terkontaminasi AFM1 (456 ng/L) kemudian ditambahkan pada ransum masing-masing hewan di kelompok A, B, C, dan D. Hasil penelitian menunjukkan bahwa tikus di Kelompok C mengalami penurunan berat badan yang signifikan (p<0,05). Packed Cell Volume (%), hemoglobin (g/dL), sel darah merah (106/mm3), Mean Corpuscular Volume (fL), Mean Corpuscular Hemoglobin (pg), dan Mean Corpuscular Hemoglobin Concentration (g/dL) tidak berbeda signifikan (p>0,05) antar kelompok yang berbeda. Kelompok C juga menunjukkan penurunan yang signifikan (p<0,05) pada jumlah sel darah putih (103/mm3) (12,90 - 8,63) dan limfosit (87,00 - 74,33%), sedangkan neutrofil (%) meningkat dari 13,00 menjadi 25,67. Berbeda dengan kelompok C, potongan jaringan pada kelompok D tidak menunjukkan lesi histologis. Oleh karena itu, Imarsil™ merupakan adsorben yang efektif dan aman untuk remediasi susu yang terkontaminasi AFM1.Kata kunci: adsorben, aflatoksin M1, ImarsilTM, parameter hematologi dan perubahan histopatologi, susu sapi